Design, Development and Installation of Jordan Subcritical Assembly - Ned Xoubi (Science and Technology of Nuclear Installations)
Following its announcement in 2007 to pursue a nuclear power program and in the absence of any nuclear facility essential for the education, training, and research, Jordan decided to build a subcritical reactor as its first nuclear facility. Jordan Subcritical Assembly (JSA) is uranium fueled light water moderated and reflected subcritical reactor driven by a plutonium-beryllium source, and the core consists of 313 LEU fuel rods, loaded into a water-filled vessel in a square lattice of 19.11 mm pitch. The fuel rods are based on PWR fuel structural pattern type, made of uranium oxide (UO2) with 3.4 wt% 235U enrichment in zirconium alloy (Zr-4) cladding. Design, optimization, and verification were performed using MCNP5 nuclear code; the computed effective multiplication factor is 0.95923. The JSA is designed to fulfill the training needs of students and is equipped to perform all of the fundamental experiments required for a typical nuclear engineering university program. This paper presents the design, development, modeling, core analysis, and utilization of Jordan’s first nuclear facility and why this simplified low cost reactor presents an attractive choice to fulfill the preliminary experimental needs of nuclear engineering education in developing countries.